Herpes Simplex Virus-1 Induced Serotonin-Associated Metabolic Pathways Correlate With Severity of Virus- and Inflammation-Associated Ocular Disease - Battaglia, Diana Marie; Sanchez-Pino, Maria D.; Nichols, Charles D.; Foster, Timothy P. (Frontiers in Microbiology, 2022)
HSV-associated diseases are a complex interaction between cytolytic viral replication and inflammation. Within the normally avascular and immunoprivileged cornea, HSV ocular infection can result in vision-threatening immune-mediated herpetic keratitis, the leading infectious cause of corneal blindness in the industrialized world. Viral replicative processes are entirely dependent upon numerous cellular biosynthetic and metabolic pathways. Consistent with this premise, HSV infection was shown to profoundly alter gene expression associated with cellular amino acid biosynthetic pathways, including key tryptophan metabolism genes. The essential amino acid tryptophan is crucial for pathogen replication, the generation of host immune responses, and the synthesis of neurotransmitters, such as serotonin. Intriguingly, TPH2, the neuronal specific rate-limiting enzyme for serotonin synthesis, was the most significantly upregulated gene by HSV in an amino acid metabolism PCR array. Despite the well-defined effects of serotonin in the nervous system, the association of peripheral serotonin in disease-promoting inflammation has only recently begun to be elucidated. Likewise, the impact of serotonin on viral replication and ocular disease is also largely unknown. We therefore examined the effect of HSV-induced serotonin-associated synthesis and transport pathways on HSV-1 replication, as well as the correlation between HSV-induced ocular serotonin levels and disease severity. HSV infection induced expression of the critical serotonin synthesis enzymes TPH-1, TPH-2, and DDC, as well as the serotonin transporter, SERT. Concordantly, HSV-infected cells upregulated serotonin synthesis and its intracellular uptake. Increased serotonin synthesis and uptake was shown to influence HSV replication. Exogenous addition of serotonin increased HSV-1 yield, while both TPH-1/2 and SERT pharmacological inhibition reduced viral yield. Congruent with these in vitro findings, rabbits intraocularly infected with HSV-1 exhibited significantly higher aqueous humor serotonin concentrations that positively and strongly correlated with viral load and ocular disease severity. Collectively, our findings indicate that HSV-1 promotes serotonin synthesis and cellular uptake to facilitate viral replication and consequently, serotonin’s proinflammatory effects may enhance the development of ocular disease.